Optimizing rheological properties for printability: low-temperature extrusion 3D printing of hydroxyapatite-polycaprolactone mixture inks for bone tissue engineering - Yan, Ming; Awad, Hani A. (Frontiers in Materials, 2023)
Low-temperature extrusion three-dimensional printing (LTE-3DP) using viscous ceramic-polymer inks has shown promise for bone tissue engineering. This process involves formulating a flowable ink by combining ceramic powders and other components with organic or inorganic polymer solutions, which can then be extruded through a 3D printer nozzle. LTE-3DP allows the incorporation of high fractions of bioactive ceramics and thermally labile additives such as drugs, proteins, and biomolecules into the inks to promote osteogenesis and bone regeneration. The rheology of the ink, influenced by various variables, significantly impacts the printability and form fidelity of the resulting scaffolds. These variables include the composition of the polymer solution and the size and weight ratio of ceramic microparticles. In this study, we posited that the printability of hydroxyapatite (HA) and polycaprolactone (PCL) mixture inks could be optimized by tailoring their rheological properties. We conducted a systematic investigation, varying the PCL weight percentage and HA:PCL weight ratio, to examine the effects of the ink's composition on its viscosity and storage modulus, as well as its printability and the mechanical properties of 3D printed HA:PCL scaffolds. We demonstrated that HA:PCL inks exhibit predictable non-Newtonian fluid behavior at higher fractions of HA, displaying significant shear thinning at elevated shear rates, which can facilitate extrusion through a 3D printing nozzle. We identified printable ink compositions based on filament continuity and scaffold form fidelity criteria. Moreover, we performed computational simulations to analyze the ink flow through an extrusion nozzle. These simulations utilized the Herschel-Bulkley-Papanastasiou constitutive model, considering the rheological properties obtained from experimental measurements. By combining experimental measurements and computational simulations, we formulated a non-dimensional Printability number that predicts whether an ink is printable based on the ink's rheological parameters and printer-specific factors. Furthermore, we evaluated the compressive properties of printed HA:PCL scaffolds and characterized the effects of PCL% and HA:PCL ratio on the hyperelasticity observed in response to compressive deformations. This hybrid approach using experimental rheology and FE simulations provides a framework to define the printability of ceramic-polymer ink formulations, which could help streamline the 3D printing of novel inks for bone tissue engineering.